Jellyfish in Pacific salmon food - A. F. Volkov (Известия ТИНРО, 2022)
Ctenophores, hydroid jellyfish, appendicularians, salpas, and the pteropoda mollusk Clione limacina, conditionally combined into the group of “jellyfish”, are found in the food of all Pacific salmon — chum salmon, pink salmon, sockeye salmon, coho salmon and chinook salmon, but only in chum salmon their share is most significant, which is shown both absolute criteria (CHIN-private index of gastric filling of certain species and groups of jelly beans) and relative (share of jelly in the total INJ-general index of stomach filling). In food, chum salmon were present in 45.0 % of samples, pink salmon — 11.0 %, sockeye salmon — 7.0 %, coho salmon — 3.3 %, chinook salmon — 1.1 %. Chum salmon is well adapted to nutrition with jelly, because. has a stomach many times larger than that of other salmon, and in the diet of gelatinous it takes first place among them. Thus, in the event of a shortage of the main food (crustaceans, fish, squid), the chum salmon, due to the ability to consume and assimilate low-calorie food in large volumes, receives additional benefits in competitive relations with salmon and other pelagic fish.